Integrating Industrial Property Education into the Curricula of Technical Studies - Angela Repanovici; Manolis Koukourakis; Ionela Maria Barsan; Dan Savescu (Knjižnica)
The paper presents some aspects and examples of handling intellectual property (IP) at universities or R&D institutes regarding how to promote and to protect innovative results or products. The first example is an outline of a strategy for the implementation of a university policy in the field of IP. The second example is the European IPEDU project and its implications in the continuing education of librarians. The project is an original initiative with ethical implications for and considerations of IP. The paper focuses on the main result of the project: the postgraduate course with five modules aimed at librarians and recent graduates to strengthen their knowledge in the field of IP and industrial property. The structure of the course and the main modules are outlined. This course is considered essential for librarians and non-law students, as understanding the wide range of relevant information and practical implications of IP is critical in today’s world of information-based careers. As a freshly accredited programme, it needs evaluation, because there has not yet been any feedback from the learners.